Effect of Spirulina Extract on Diazinon Effect at the Channel Membrane Albumin and Vitelin Membranes Based on Strong Flows and Voltage - Dian Rizqi Nur Amalia; Abdurrouf Abdurrouf; Unggul P. Juswono (Natural B, Journal of Health and Environmental Sciences, 2017)
The use of pesticides in foods can be bad for human health, so the danger of pesticide use in food can damage cell metabolism or permeability of the cell membrane. This study aims to analyze the effect of Spirulina extract on the potential difference of egg cell membrane of albumin and vitellin chickens against anti channel blocker on diazinon. The contaminant used in this research is diazinon 600 EC. How to overcome the contamination of livestock products that can be harmful to health one of them using antioxidants. Thus, the administration of Spirulina extract can affect the potential response of egg cell membranes (Gallus Gallus domesticus) in the polluted food of diazinon. Potential rabbit egg membrane can be measured by using microelectrode associated with PicoScope 5000 series, then the data appears will be displayed through the PC. The results of this measurement showed that along with the increase of diazinon solution concentration, the potential value of egg cell membrane produced decreased. While the influence of Spirulina extracts in the egg (Gallus gallus domesticus) membrane that has been contaminated diazinon showed the potential value of membrane bigger/higher. This is because in the extract Spirulina has phenolic and flavonoid content that has the potential as an antioxidant that can be useful to reduce the level of free radical reactivity caused by diazinon.